Waterbirds diversity in Peniti mangrove forest, Pontianak Regency - DEWI ELFIDASARI; JUNARDI JUNARDI (Biodiversitas Journal of Biological Diversity, 2006)
The aim of this research was to know waterbirds diversity in the Peniti mangrove forest, Pontianak Regency. This research was found 19 species (9 families) of waterbirds that living in the Peniti mangrove forest, Pontianak Regency, West Kalimantan. This identification showed that four species were member of Sternitidae Family, three species were member of Ardeidae Family, other three species were member of Anatidae Family, two species were member of Laridae Family, two species from Accipritidae Family, and Alcedinidae Family. One species from Ciconidae Family, Scolopacidae Family, and Ploceidae Family. Thirteen species of them were protected in Indonesia; there were Egretta garzetta, E. sacra, Ardea cinerea, Ciconia episcopus, Larus ridibundus, L. brunnicephalus, Sterna sumatrana, S. dougallii, Anous minutus, Gygis alba, Halcyon pileata, Todirhamphus chloris, and Lonchura fuscans. Lochura fuscans was belonging to Indonesian endemic birds, because we only found this bird species in Kalimantan Islands. Two species, Haliaetus leucogaster and Haliastur indus were the International protected species according to Appendix II Convention on International Trade in Endangered Species (CITES). Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: waterbirds, protected, endemic, species.